Socio‐Economic Inequalities in Health Care in England1. (September 2016) - Cookson, Richard; Propper, Carol; Asaria, Miqdad; Raine, Rosalind
Abstract: This paper reviews what is known about socio‐economic inequalities in health care in England, with particular attention to inequalities relative to need that may be considered unfair ('inequities'). We call inequalities of 5 per cent or less between the most and least deprived socio‐economic quintile groups 'slight', inequalities of 5–15 per cent 'moderate' and inequalities of more than 15 per cent 'substantial'. Overall public health care expenditure is substantially concentrated on poorer people. At any given age, poorer people are more likely to see their family doctor, have a public outpatient appointment, visit accident and emergency, and stay in hospital for publicly‐funded inpatient treatment. After allowing for current self‐assessed health and morbidity, there is slight pro‐rich inequity in combined public and private medical specialist visits but not in family doctor visits. There are also slight pro‐rich inequities in overall indicators of clinical process quality and patient experience from public health care, substantial pro‐rich inequalities in bereaved people's experiences of health and social care for recently deceased relatives, and mostly slight but occasionally substantial pro‐rich inequities in the use of preventive care (for example, dental check‐ups, eye tests, screening and vaccination) and a few specific treatments (for example, hip and knee replacement). Studies of population health care outcomes (for example, avoidable emergency hospitalisation) find substantial pro‐rich inequality after adjusting for age and sex only. These findings are all consistent with a broad economic framework that sees health care as just one input into the production of health over the life course, alongside many other socio‐economically patterned inputs including environmental factors (for example, living and working conditions), consumption (for example, diet and smoking), self‐care (for example, seeking medical information) and informal care (for example, support from family and friends).